Right versus left heart reverse remodelling after treating ischaemic mitral and tricuspid regurgitation. (14th November 2020) - Elgharably, Haytham; Javadikasgari, Hoda; Koprivanac, Marijan; Lowry, Ashley M; Sato, Kimi; Blackstone, Eugene H; Klein, Allan L; Gillinov, A Marc; Svensson, Lars G; Navia, José L
Abstract: OBJECTIVES: Repair outcomes of tricuspid regurgitation (TR) associated with ischaemic mitral regurgitation (IMR) are inferior to functional TR in terms of TR recurrence and right ventricular (RV) reverse remodelling. Our objective is to analyse right versus left heart reverse remodelling after surgery for IMR-associated TR. METHODS: From 2001 to 2011, 568 patients with severe IMR underwent mitral valve surgery (repair 87%, replacement 13%), and 131 had concomitant tricuspid valve repair. Median follow-up was 3.0 years; 25% of living patients were followed up for 6.3 years. Longitudinal analysis of 1527 follow-up echocardiograms was performed to assess ventricular reverse remodelling and function. RESULTS: Unlike the left heart, the right heart failed to reverse remodel (failed to recover ventricular function or halt dilatation). During follow-up after surgery, the right ventricle continued to dilate while the left ventricle regressed in size. RV ejection fraction decreased (46% at 1 month and 44% at 5 years), while left ventricular ejection fraction increased (33% and 37%, respectively). RV strain showed early (−11% at 1 month) and late (−12% at 5 years) dysfunction. Patients who underwent tricuspid valve repair had worse RV function. Mitral regurgitation remained stable after surgical intervention, and TR gradually recurred (37% moderate, 20% severe at 7 years). CONCLUSIONS: Surgical treatment of IMR and TR along with revascularization failed to induce reverse remodelling of the right heart. These findings warrant further investigations to identify optimal timing and approach of intervention for IMR-associated TR with respect to RV remodelling. Abstract : Interest in addressing functional tricuspid regurgitation (TR) at the time of left-heart surgery has been growing, with long-term results suggesting low recurrence of TR and subsequent right-heart reverse remodelling [1–4].